Current forensic psychiatry and medical ethics - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
The action of crime and the interaction of individuals with a crime on a personal and societal basis constitute the topic of forensic psychiatry. Despite the fact that the primary purpose of the forensic psychiatrist is to make an evaluation of the patient so as to respond to the questions that are being asked by the court, medical ethical rules have to be in place in all applications of the forensic psychiatrist. Such activities are administered by way of regulations that are formed within organizations and through the activities of professional bodies and related organizations that include experts in each country. All the general rules that apply for medical ethics apply for applications of psychiatry as well. According to what is stated in the Declaration of the World Medical Association, the physician should first consider the advantage of his patient. However, when crimes such as sexual assault, murder or child abuse that are perpetrated against humanity are being hidden, or when the perpetrators are protected or hidden, the situation does not coincide with ethical principles. © 2021 Nova Science Publishers, Inc.